Gel polymer electrolyte based on PVDF-HFP:PMMA incorporated with propylene carbonate (PC) and diethyl carbonate (DEC) plasticizers : electrical, morphology, structural and electrochemical properties - Khushbu Gohel; D K Kanchan; Hiren K Machhi; Saurabh S Soni; C Maheshwaran (Materials Research Express, 2020)
To overcome the drawbacks of organic solvent−based liquid electrolytes and a solid polymer electrolyte as a separator in lithium polymer battery, in the recent study gel polymer electrolyte (GPE) using poly(vinylidene fluoride− hexafluropropylene) (PVDF−HFP) and poly (methyl methacrylate) (PMMA) as host polymers, lithium perchlorate (LiClO _4 ) salt as conducting species and propylene carbonate (PC) and diethyl carbonate (DEC) plasticizers as an organic solvent has been prepared. The solution casting technique has been adopted to fabricate gel polymer electrolyte (GPE). The prepared GPE films were analyzed using different experimental techniques to discover the properties of GPE. The ionic conductivity of GPE films has been carried out using electrochemical impedance spectroscopic technique. The maximum ionic conductivity of 3.97E-4 S cm ^−1 has been obtained for GPE having 60 wt% PC:DEC. As an evidence of change in ionic conductivity, structural characterization has been analyzed using FTIR and SEM where, FTIR spectra reveal complex formation taking place between polymers, salt, and plasticizers and SEM micrograph shows a change in surface morphology with a change in plasticizers amount. Dielectric analysis has been also carried out in terms of dielectric constant ( ${ε }^{{′} }$ ) and dielectric loss ( ${ε }^{{′′} }$ ). Cyclic voltammetry (CV) has been applied to find electrochemical stability window.